Eksistensi Literatur Tafsir Nusantara-Indonesia dalam Tafsir al-AzharKarya Hamka - Arivaie, Rahman; Erdawati, Sri; Wahidi, Ridhoul (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2021)
This paper attempts to explore the Indonesian-Indonesian interpretation literature contained in the Tafsir al-Azhar by Haji Abdul Malik Karim Amrullah (Hamka). This research was conducted to detect the existence, intensity, and involvement of the Nusantara-Indonesian interpretations as a reference for the writing of Tafsir al-Azhar. After conducting a search, it was found that the literature on the interpretation of the Archipelago-Indonesian in Tafsir al-Azhar was very varied. The author classifies them into four categories. First, the exegetical literature written explicitly in the commentary text and listed in the bibliography of Tafsir al-Azhar, consists of 4 works of commentary. Second, the exegetical literature written explicitly in the commentary text, but not listed in the bibliography, consists of one work of commentary. Third, literature that is not written explicitly in the text of commentary, but is listed in the bibliography, this category consists of three works of interpretation. Fourth, exegetical literature that is not written explicitly in the text of commentary or in the bibliography or is referred to as "ignored interpretation" literature. Even though it is very possible to be used as a reference for writing Tafsir al-Azhar, which falls into this category consists of three works of interpretation.